Chemical Profiling and Biological Screening of Some River Nile Derived-Microorganisms - Lotfy, Momen M.; Hassan, Hossam M.; Mohammed, Rabab; Hetta, Mona; El-Gendy, Ahmed O.; Rateb, Mostafa E.; Zaki, Mohamed A.; Gamaleldin, Noha M. (Frontiers in Microbiology, 2019)
Abstract Aims: Chemical and biological studies of the River Nile derived-microorganisms are limited. Hence, this work was carried out to screen the River Nile habitat. Identification of the isolated organisms, chemical profiling of their ethyl acetate extracts as well as screening of their antimicrobial, antileishmanial, antitrypanosomal, and antimalarial activities were investigated. Methods: Identification of the microbial isolates were carried out using bacterial 16S rRNA and fungal 18S rRNA gene sequencing. Chemical profiling of the EtOAc extracts using LC-HRESIMS spectroscopy was carried out. The in vitro antimicrobial screening using the modified version of the CLSI method, antileishmanial and antitrypanosomal activities were screened using Leishmania donovani promastigote assay, L. donovani axenic amastigote assay, Trypanosoma brucei trypamastigotes assay and THP1 toxicity assay. The in vitro antimalarial activities against D6 (chloroquine sensitive) and W2 (chloroquine-resistant) strains of Plasmodium falciparum were evaluated. Results: Seven isolated microorganisms were identified as Streptomyces indiaensis, Bacillus safensis, Bacillus anthracis, Bacillus spp. and Aspergillus awamori. Chemical investigation of different extracts showed several bioactive compounds, identified as; nigragillin, 5-caboxybenzofuran and dyramide B from Aspergillus awamori and actinopolysporin B from Streptomyces indiaensi. On the other hand many nitrogenous compounds with high molecular weights showed no hits that may correspond to new long chain and/or cyclic peptides. The EtOAc extract of Bacillus safensis fermentation broth showed the highest activity against Plasmodium falciparum D6 and P. falciparum W2 (IC50 = 25.94 and 27.28 μg/mL, respectively), while two isolates Streptomyces indiaensis and Bacillus spp. RN-011 extracts showed the highest antitrypanosomal activity (IC50= 0.8 and 0.96 µg/mL). Conclusion: The River Nile could be a new source for production of promising bioactive leading compound where antimicrobial and antiparasitic activities may be correlated.